2019
DOI: 10.1111/pcn.12901
|View full text |Cite
|
Sign up to set email alerts
|

Neural mechanisms underlying adaptive and maladaptive consequences of stress: Roles of dopaminergic and inflammatory responses

Abstract: Stress caused by adverse and demanding conditions, a risk factor for mental illnesses, induces adaptive or maladaptive neural and behavioral consequences, depending on the conditions. Studies using rodent stress models have revealed multiple mechanisms related to dopamine and inflammation for stress-induced neural and behavioral changes. Thus, repeated stress alters activities of ventral tegmental area dopamine neurons projecting to the nucleus accumbens and the medial prefrontal cortex in distinct manners. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…While several empirical studies have shown the effect of stressors on stress consequences ( Davey et al, 2016 , Furuyashiki and Kitaoka, 2019 , Gillespie et al, 2001 , Lowe et al, 2017 ), the underlying mediating and moderating mechanisms remain less clear. Investigating the degree to which these underlying mechanisms of the stress consequences of college students under the pressure of COVID-19 is vitally important.…”
Section: Discussionmentioning
confidence: 99%
“…While several empirical studies have shown the effect of stressors on stress consequences ( Davey et al, 2016 , Furuyashiki and Kitaoka, 2019 , Gillespie et al, 2001 , Lowe et al, 2017 ), the underlying mediating and moderating mechanisms remain less clear. Investigating the degree to which these underlying mechanisms of the stress consequences of college students under the pressure of COVID-19 is vitally important.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Bureau of Economic Analysis's Health care Satellite Account, in 2013 in the USA ~$89 billion has been spent on the treatment of mental illnesses (33). In the past years, many studies have focused on understanding the mechanisms underlying mental illness (34)(35)(36)(37)(38)(39); much of the literature has analyzed the role of the monoaminergic system, in particular, the serotonin and catecholamine involvement in the etiology of these pathologies (40)(41)(42). The impairment of the monoaminergic system alone cannot explain all the aspects related to these diseases, since over the years it has become increasingly clear the contribution of other players such as PAs (43).…”
Section: Polyamines and Mental Disordersmentioning
confidence: 99%
“…In the hippocampus (HPC) and prefrontal cortex (PFC), psychosocial stress increases the levels of extracellular ATP, which induces the NLRP3-dependent inflammasome, leading to microglial interleukin IL-1b release (Pantazatos et al, 2017). Likewise, toll-like receptors TLR-2 and TLR-4 can mediate repeated stress-induced gene expression and TNF-a/IL-1a secretion from the PFC microglia (Wohleb et al, 2012;Nie et al, 2018;Furuyashiki and Kitaoka, 2019). Finally, restraint stress induces alterations to neurotransmitters such as glutamate and GABA, which influence microglial activation, proliferation, and motility (Nair and Bonneau, 2006;Fontainhas et al, 2011).…”
Section: Causal Factors Of Immune Dysregulation In Mental Disordersmentioning
confidence: 99%